Memberdayakan Perpustakaan Sekolah - Mashuri, Ilham (STAIN Ponorogo, 2010)
Problem of a quality of school education has always been an interesting theme for discussion. But one thing that is still unnoticed by the education experts is the problem of the role of libraries in schools. The library is important. Everyone acknowledges that, as well as importance of readning,. however people rarely think of how students are encouraged to like readning and make it as a culture. The education quality should be supported by an adequate library. Therefore, there must be a synergy among the various components of education in scholls to start readning habits from managing the library. This short article tries habits from how to empower the library that canÂ compel students to like reading very much so that it will impact undirectly on the improvement of education quality in school.